The Occurrence of Major Viruses Infecting Zucchini Squash (Cucurbita pepo L.) in Morocco - Afechtal, Mohamed; Aarabe, Ahmed; Chebli, Bouchra; Mounir, Majid (European Scientific Journal, ESJ, 2019)
Zucchini squash, Cucurbita pepo L., is one of the most economically important vegetable crops in Morocco. Virus diseases are a major factor in limiting production of zucchini squash in the country. During the growing seasons 2015, 2016 and 2017, the main areas of field-grown cucurbit production in Morocco (Loukkos, Gharb, Bouznika, Doukkala and Souss) were surveyed for the occurrence and distribution of viruses of zucchini squash. A total of 38 commercial fields were visited and inspected for symptoms of virus diseases and 415 leaf samples were collected from plants showing virus-like symptoms for laboratory analyses. ELISA technique was used to detect the following viruses: Zucchini yellow mosaic virus (ZYMV), Squash mosaic virus (SqMV), Cucumber mosaic virus (CMV), Papaya ringspot virus-watermelon strain (PRSV-W) and Cucurbit aphid-borne yellows virus (CABYV). The obtained results showed that virus diseases were widely distributed in the country with an infection rate of 77.6%, especially in the region of Loukkos where 85% of the tested plants were infected by at least one virus. To the best of our knowledge, this isthe first study on the occurrence and geographical distribution of viruses infecting zucchini squash in Morocco. This study provides valuable information, which could be beneficial and of great interest for the researchers, growers and the plant protection services for planning future strategies to control virus diseases of zucchini squash in Morocco.